Clinical Impact of Hydrocortisone Uses on Patient with COVID-19: A Case Report - G. C. Owhonda; T. I. Nonju; C. N. Eze-Emiri; V. Oris-Omini (Archives of Current Research International, 2023)
COVID-19 can cause anything from no symptoms at all to severe breathing problems, organ failure, and even death. Currently, there is no cure for COVID-19, thus treatment focuses on providing the patient with as much comfort as possible. Hydrocortisone are utilized for patients with acute respiratory disease syndrome and septic shock because they shorten the need for mechanical ventilation, ICU stay, and perhaps mortality. This prospective case report study showed the intravenously administered Hydrocortisone response on a patient admitted to the Elekahia COVID-19 treatment centre, located in Port Harcourt, Rivers State, Nigeria. The patient was a 47-year-old man of Asian descent; he presented with pneumonia-like symptoms and developed severe breathlessness. Treatment started on 6th June 2020 and ended on 16th June 2020. There was a marked improvement in peripheral capillary oxygen saturation (SpO2) after hydrocortisone intervention; respiratory rate reduced from 40 cycles per minute to 18 cycles per minute, and the patient could complete sentences without developing breathlessness, three hours after receiving the first dose of intravenous hydrocortisone. The use of Hydrocortisone therapy could be of tremendous benefit in the treatment of COVID-19 patients who present with severe respiratory distress. Controlled randomized clinical trials are required to assess steroid use in COVID-19 treatment properly. And to assess its use as a prophylactic in the early management of severe COVID-19 cases.